Analytical Hierarchy Process for Selecting the Locations for Vegetable Vendors - Chakraborty, Sushmita; Bandyopadhyay, Abir; Sthapak, Swasti (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Choosing the right location is crucial for the success of any business, and this holds true worldwide. While there has been extensive research on location selection for any business setup, very limited study has been done to identify suitable locations for vegetable vendors, particularly in urban areas. To address this gap, present study aims to establish a methodology to identify the most suitable locations for vegetable vendors in urban area using the Analytical Hierarchy Process (AHP). AHP establishes the criteria and attributes for identifying the best locations for vegetable vendors in the present study. From the existing literature, four criteria and eleven attributes were selected. The relative relevance of these criteria and attributes are determined using AHP. Findings of the present study, established that accessibility, environment, infrastructure, and population are the crucial aspects to be considered while predicting suitable locations for vegetable vendors. The findings of this study will provide significant insights to urban planners, municipal officials, and development authorities for identifying or anticipating the appropriate locations for vegetable vendors in urban areas.